Konstruksi wacana dan realitas portal berita online - Achfandhy, Mochammad Irfan (Islamic Communication Journal, 2021)
The Reunion 212 action is a socio-religious movement that has generated controversial responses in various circles of society. The problem is caused by the reporting of every online media which is not always neutral and coherent with the existing social reality. In addition, online media are often used to construct a group discourse to the public. This study aims to uncover the motives for reporting the 212 Reunion Action from the online news portal Republika. The research method uses a descriptive qualitative approach and uses critical discourse analysis by Teun A. Van Dijk. The data is taken from Republika's news coverage from November to December about the 212 Reunion Action. The findings of the research show that Republika does not publish the news of the 212 Reunion Action group as a whole. Some of the information that is not uploaded in the narrative of the news text is of propaganda value which aims to form the group's image and as an accommodation effort to reduce the negative public response and the discourse is built positive views. However, the inconsistency of the news has shown the assumption of a shift in the media as a source of information into the media as a space for the existence and contestation of a group. the recommendation is that media repositioning is needed to open a wider space so that the media can again become a source of information for the community that is free of elements or independent media.Â